Equal Positions for Rural Youth: Education and Technology in the Province of Salta (Argentina) - Chachagua, María Rosa (2020)
DOI: 10.26439/contratexto2020.n033.4784 Longing for a more equal society implies thinking about emancipatory public policies that can be applied in all population areas, especially in rural areas. Education is one of the fundamental tools for the development of a country, which implies that access is a priority right at all levels (Gentili, 2009). And this right includes the possibility of enter to the educational system, studying, appropriating, growing, progressing and finally graduating to dream of a better future. Our main objective is to analyze the different dimensions of inequality: socio-economic, digital and gender, in rural areas. In this sense, the idea of​​ equality of positions, raised by Dubet (2011), is put into discussion, taking as a case study the young people who attend the Rural Secondary School Mediated by Technologies (ERMT) in the province from Salta (Chachagua, 2019). Anotherobjective is to investigate what happens to the notion of youth in this area, for that the different perspectives of this concept are put into dialogue, anchoring it in a specificterritory. Finally, we take the experience of field work, to think about collective construction proposals related to education and technology in rural areas. Proposals thatarise from the voices of the actors themselves (students, teachers, workers) imagining in future scenarios more egalitarian and with greater (and better) possibilities for all.